"The Star" for Beginners Introductions to the Magnum Opus of Franz Rosenzweig - Brasser, Martin; Paolo Ciglia, Francesco; Bojanić, Petar D. (Ubiquity Press, 2021)
In "The Star of Redemption", written at the end and after World War I and published in 1921, Franz Rosenzweig presented an epoch-making Jewish-inspired philosophy of religion. In three steps, each with three chapters or "books," Rosenzweig unfolds in it his view of God, the world, and man, their interrelationship, and their contribution and role in the redemption of the world. In this introduction, young and old Rosenzweig scholars take readers by the hand chapter by chapter, book by book. They lead safely through Rosenzweig's argumentation, making sometimes difficult lines of thought comprehensible and plausible. The chapter introductions open up reliable access for interested readers and new perspectives for connoisseurs.